Encounters and places: Project negotiations in Galessa, Ethiopia - Habermann, Birgit; Felt, U.; Vogl, C.R.; Bekele, K.; Mekonnen, Kindu (Emerald Publishing Limited, 2012)
Purpose – Reflections on negotiation processes between farmers and scientists in research projects provide insights into issues of participation, power and equity. The purpose of this paper is to illustrate how actors chose places to meet, negotiate and represent technologies. Design/methodology/approach – The research involved semi-structured interviews and participant observation with farmers, scientists, government agricultural advisors (extensionists), policymakers, and staff of development organisations involved in a research for development project in Western Shewa, Ethiopia from 2009 to 2011. It combines theories from social studies of science as well as development studies. Findings – Using blueprint approaches in research projects will not yield sustainable results. Participation must go beyond consultation or trying to educate farmers. Social relations are at the core of cooperation between farmers and scientists and require much more attention. Powerful choices on modes of representation and communication technologies as well as unilateral decisions on places have important implications for the way decisions are eventually made and by whom. Originality/value – This approach to studying research for development projects from social studies of science perspectives adds new insights into debates on participation and power in technology transfer and multicultural cooperation in rural development.